Comparative Absorption of 5-Aminosalicylic Acid (5-ASA) after Administration of a 5-ASA Enema and Salazosulfapyridine (SASP) after an SASP Suppository in Japanese Volunteers - Tokui, Kenji; Arakawa, Toshiharu; Matsumoto, Takatoshi; Nabeshima, Toshitaka; Asai, Yoshitaka (Biological & pharmaceutical bulletin, 2002)
Salazosulfapyridine (SASP) is widely used orally and rectally in the treatment of ulcerative colitis. SASP is mainly metabolized by hydrolysis and the main active metabolite, 5-aminosalicylic acid (5-ASA), has an antiinflammatory effect. In the present study, we prepared suppositories containing 6.5 mmol of SASP and an enema containing 6.5 mmol of 5-ASA. We measured the concentrations of SASP and its various metabolites, 5-ASA, sulfapyridine (SP), acetylated metabolite of SP (Ac-SP), and N-acetyl-5-ASA (Ac-5-ASA), in the serum and urine after a single administration of each preparation to healthy male volunteers. When the SASP suppository was administered, the maximum concentration (Cmax) of SASP and Ac-5-ASA was 2.5±0.4 and 0.5±0.2 µM and the time to Cmax (Tmax) was 5 and 12 h, respectively. The Cmax value of SP, which causes side effects, was one-half of that of the parent compound. No 5-ASA in the serum was observed. When the 5-ASA enema was administered, Cmax and Tmax values of 5-ASA and Ac-5-ASA were 5.8±2.0 and 13.3±3.6 µM and 1 and 7 h, respectively. The area under the serum concentration–time curve (AUC) of SASP was 27.4±4.8 µM·h, a finding similar to that of 5-ASA after the administration of the 5-ASA enema (29.4±11.1 µM·h). The percentage of urinary recovery of SASP 24 h after administration of the SASP suppository was approximately 0.2%. These results indicate that SASP administered rectally is almost completely hydrolyzed in the colon and that 5-ASA is partially absorbed from the small intestine in unchanged form. On the other hand, approximately 0.3% of 5-ASA was recovered in the urine in unchanged form after the administration of the 5-ASA enema, whereas the urinary recovery of Ac-5-ASA was more than 10%. The present findings suggest that 5-ASA has favorable absorptive properties and can be expected to have systemic action after rectal administration of a 5-ASA enema.